Motivational Factors for Halal Certification Adoption among Small and Micro Enterprises in Malaysia - Nur Shuhada Abdul basir; Chemah Tamby chik; Sabainah Bachok; Noradzhar Baba; Rasidah Hamid; Maria Mohd salleh (International Journal of Supply Chain Management, 2018)
The halal food industry is vital to the world wide muslim consumers to ensure the food they consumed, use and purchase are hygienic, clean and not harmful to health. Muslim is the largest group in Malaysia with 61.3% from total population. Thus, having halal products are important in Malaysia. However, halal is not just for the muslim, the process of producing halal product may well benefit non muslim all around the world. Therefore, the markets for halal product are huge beyond the consumption of Malaysian population. But the capabilities of exporting halal products among small and micro enterprises in Malaysia are still weak. Therefore, this research intends to study the motivational factors that influence or hinders halal certification adoption among small and micro companies. It is designed to investigate the connection between motivational factors towards halal certification adoption, to study if expected competitiveness affects halal certification adoption, and to what extent top management commitment impacts the halal certification adoption. This study could add knowledge and help government in introducing policy to encourage these companies to embark in the halal journey.